Modern information technology in the teaching of pharmacognosy - V. S. Dolya; V. I. Mosul; А. V. Mazulin (Zaporožskij Medicinskij Žurnal)
Sets out guidelines for the teaching of pharmacognosy at Zaporozhye State Medical University for credit-modular system, which contributes to students' motivation to learn throughout the training period. The use of modern information technologies in teaching Pharmacognosy.